Information and Communication Technologies (ICT) in Public School Management in Cuito – Bié, Angola (Research, Society and Development, 2026)
The objective of this study is to analyze the impact of Information and Communication Technologies (ICT) on the quality of school management in public schools linked to the Municipal Education Directorate of Cuíto – Bié, Angola, from 2023 to 2025. ICT supports school managers in organizing tasks, improving planning, and monitoring teaching development. It assists teachers and optimizes local administrative processes. Teachers use digital resources such as software, co-planning, grade recording, pedagogical monitoring, and formative assessment. The study employs a mixed methodology, combining qualitative and quantitative analysis. Challenges include resistance, limited resources, insufficient training, inadequate infrastructure, pedagogical adaptation, management, communication, engagement, evaluation, and school planning. I will apply Chris Argyris's Participative Management Theory, emphasizing participation, communication, and continuous school improvement. Argyris's theory guides participative management. It focuses on communication and collaborative decision-making. The study faces time constraints. Available resources are insufficient. The sample size is limited. Secondary data presents inconsistencies, affecting reliable results. The aim is to improve performance, participation, and efficiency.